Shape Optimization of Mufflers Composed of Multiple Rectangular Fin-shaped chambers Using Differential Evolution Method - Min-Chie CHIU; Ying-Chun CHANG; Wei-Ting TAI (Archives of Acoustics, 2015)
There has been considerable research done on multi-chamber mufflers used in the elimination of industrial venting noise. However, most research has been restricted to lower frequencies using the plane wave theory. This has led to underestimating acoustical performances at higher frequencies. Additionally, because of the space-constrained problem in most plants, the need for optimization of a compact muffler seems obvious. Therefore, a muffler composed of multiple rectangular fin-shaped chambers is proposed.